Atlas of pulmonary pathology : a pattern based approach - Butt, Yasmeen M; Tazelaar, Henry D (Wolters Kluwer, 2022)
"Closely mirroring the daily sign-out process, Atlas of Pulmonary Pathology: A Pattern Based Approach is a highly illustrated, efficient guide to accurate diagnosis. This practical reference uses a proven, pattern-based approach to clearly explain how to interpret challenging cases by highlighting red flags in the clinical chart and locating hidden clues in the slides. Useful as a daily "scope-side guide," it features numerous clinical and educational features that help you find pertinent information, reach a correct diagnosis, and assemble a thorough and streamlined pathology report. More than 1,600 high-quality photomicrographs capture the subtle morphologic spectrum of both neoplastic and non-neoplastic lung biopsies. Each image is captioned with key diagnostic considerations and includes callouts showing subtle features and diagnostic clues.Practical tools throughout the text include:Tables that emphasize salient clinicopathologic features, management implications, and therapeutic optionsDiscussions of how and when to incorporate molecular toolsChecklists for key elements of the diagnostic approach and sample notes for inclusion in pathology reportsRelevant endoscopic images, photographs of select gross specimens, and medical figuresBrief reviews of normal histology that provide contrast to succeeding patterns"Pearls and Pitfalls" and "Near Misses" sections with lessons from real life sign-out experience "Frequently Asked Questions" sections that discuss common diagnostic dilemmas "Sample Note" sections that offer a template of how to sign out cases from the simple to the complexComprehensive quiz provides experience with high-yield, board-style teaching topics Enrich Your eBook Reading ExperienceRead directly on your preferred device(s), such as computer, tablet, or smartphone.Easily convert to audiobook, powering your content with natural language text-to-speech"--
Keywords: pneumologie; patologie; Pulmonary Medicine; Pathology; Lung Diseases; plicní nemoci